Sensory Profiling of Commercial Sweet Crackers Using Check-All-That-Apply and Just-About Right Methods - Hunaefi, Dase; Putri, Danica; Indrasti, Dias; Fuhrmann, Philipp; Smetanska, Iryna (Jurnal Teknologi dan Industri Pangan, 2025)
This study employed a dual-sensory technique to assess six commercially available sweet cracker products. The just-about-right (JAR) method was used to measure ideal intensity, while the check-all-that-apply (CATA) method was employed to determine attribute presence. A focus group discussion generated a lexicon of eighteen descriptors, from which six essential attributes, coarseness, roughness, creaminess, milkiness, sweet aftertaste, and grittiness, were selected for the JAR evaluation. In a randomized home-use test (HUT), thirty-three Indonesian panelists evaluated these attributes. JAR data were analyzed for deviation percentages and penalty effects on overall liking, while CATA responses were subjected to Cochran’s Q test with Bonferroni-adjusted McNemar comparisons. The findings indicate that adjusting attribute intensities to align with panelists’ ideals significantly improves acceptability, particularly for sample 363. Recommen-dations are provided for improving the formulation.